Quantification of the perceived training load and its relationship with changes in physical fitness performance in junior soccer players - Gil-Rey, E.; Lezaun, A.; Los Arcos, A. (Journal of Sports Sciences, 2015)
The aim of this study was to determine the relationship between perceived respiratory and muscular training load (TL) and changes in physical fitness in elite and non-elite junior soccer players. Twenty-eight elite (n = 14, 17.6 ± 0.6 years, 70.3 ± 4.4 kg, 179.7 ± 5.6 cm) and non-elite (n = 14, 17.5 ± 0.5 years, 71.1 ± 6.5 kg, 178.1 ± 5.6 cm) soccer players belonging to a Spanish first and third division football academies and competing in junior Spanish first division (2012-2013) participated in the study. Countermovement jump (CMJ), CMJ arm swing, 5 and 15 m sprints and the Université de Montreal endurance test were performed in January and 9 weeks later in March. In order to quantify TLs, after each training session and match, players reported their session rating of perceived exertion (sRPE) separately for respiratory (sRPEres) and leg musculature (sRPEmus). Elite players accumulated greater weekly training volume (361 ± 14 vs. 280 ± 48 min; effect sizes (ES) = 5.23 ± 1.74; most likely), and perceived respiratory (1460 ± 184 vs. 1223 ± 260 AU; ES = 1.12 ± 0.79; very likely) and muscular (1548 ± 216 vs. 1318 ± 308 AU; ES = 0.99 ± 0.84; likely) TL than did non-elite players. Training volume, sRPEres-TL and sRPEmus-TL were positively and largely correlated (r = 0.67-0.71) with the changes in aerobic fitness. The present results suggest that a low training volume and TL can impair improvement in aerobic fitness in junior soccer players during the in-season period.